Evaluation of Educational Tourism at Mangkunegaran Museum - Made Prasta Yostitia Pradipta; Heddy Shri Ahimsa Putra; Tri Kuntoro Priyambodo; Hendrie Adji Kusworo (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2025)
This study evaluates the effectiveness of educational tourism at the Mangkunegaran Museum by highlighting five main dimensions: digital interpretation, guide education quality, authenticity and conservation, facility inclusivity, and cognitive impact. The research method uses source triangulation (managers, guides, tourists) and method triangulation (observation, interviews, documentation) to ensure data validity. The results show a significant gap between global standards for modern museums and the actual conditions at Mangkunegaran. Digital interpretation is not yet available, so visitors rely on verbal explanations. The guides are skilled at storytelling based on local wisdom, but the narratives are still descriptive and lack pedagogical value. The authentic collections are not accompanied by transparent conservation practices, so visitors do not understand the preservation process. Inclusive facilities are limited due to the historic architectural structure, which makes it difficult for people with disabilities and the elderly to access. The cognitive impact on visitors is relatively low because the learning experience is more superficial, although interactive activities such as dance and batik workshops have been shown to increase positive perceptions of Javanese culture. The conclusion emphasises the need for a development strategy through the digitisation of collections, capacity building for guides, participatory conservation, the provision of inclusive facilities, and interactive programmes. This transformation will make the Mangkunegaran Museum not only a space for preserving artefacts, but also an adaptive and relevant cultural learning centre for future generations.